2020
DOI: 10.1002/adfm.202002462
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Doping Improves the Immobilization and Catalytic Effects of Co9S8 in Li‐S Batteries

Abstract: Several critical issues, such as the shuttling effect and the sluggish reaction kinetics, exist in the design of high‐performance lithium–sulfur (Li‐S) batteries. Here, it is reported that nitrogen doping can simultaneously and significantly improve both the immobilization and catalyzation effects of Co9S8 nanoparticles in Li‐S batteries. Combining the theoretical calculations with experimental investigations, it is revealed that nitrogen atoms can increase the binding energies between LiPSs and Co9S8, and as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 71 publications
3
83
0
Order By: Relevance
“…For the Co 2 p spectra of Co 9 S 8 , the peaks at 778.5 and 793.6 eV correspond to Co 3+ in Co 2 p 3/2 and Co 2 p 1/2 , respectively, and the peaks at 781.6 and 797.6 eV correspond to Co 2+ in Co 2 p 3/2 and Co 2 p 1/2 , respectively, in Figure 3c. [ 41,52,53 ] For the composite, a pair of new characteristic peaks appeared at 780.8 and 796.8 eV. The close results show that the characteristic peaks appear at 779.8 and 794.8 eV in the Co 2 p spectra of pure CoN (Figure S5a, Supporting Information).…”
Section: Resultsmentioning
confidence: 65%
“…For the Co 2 p spectra of Co 9 S 8 , the peaks at 778.5 and 793.6 eV correspond to Co 3+ in Co 2 p 3/2 and Co 2 p 1/2 , respectively, and the peaks at 781.6 and 797.6 eV correspond to Co 2+ in Co 2 p 3/2 and Co 2 p 1/2 , respectively, in Figure 3c. [ 41,52,53 ] For the composite, a pair of new characteristic peaks appeared at 780.8 and 796.8 eV. The close results show that the characteristic peaks appear at 779.8 and 794.8 eV in the Co 2 p spectra of pure CoN (Figure S5a, Supporting Information).…”
Section: Resultsmentioning
confidence: 65%
“…As evidenced by the typical charge/discharge profiles within 1.6–2.8 V versus Li + /Li, the contributions of N‐Co 9 S 8 or Co 9 S 8 to the total capacity can be neglected. [ 96 ]…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…[135,136] To further boost the capture of PS on Co 9 S 8 , Liu et al reported the synthesis of N-doped Co 9 S 8 nanoparticles (N-Co 9 S 8 ). [137] Figure 8a depicts the optimal adsorption configurations of PS intermediates on both (311) and (440) lattices of N-Co 9 S 8 and Co 9 S 8 , respectively. It is noted c) Reproduced with permission.…”
Section: Anion-doped Compoundmentioning
confidence: 99%
“…[139] Of note, the bond lengths of various sulfur species (Li c) Reproduced with permission. [137] Copyright 2020, Wiley-VCH. d) Potentiostatic discharge profiles of Li 2 S 8 /tetraglyme solution at 2.05 V. e) Dissociation barriers and pathways of Li 2 S cluster.…”
Section: Anion-doped Compoundmentioning
confidence: 99%
See 1 more Smart Citation